Micturition and the mind: psychological factors in the aetiology and treatment of urinary symptoms in women. Issue 6571 (28th February 1987) - Macaulay, A J; Stern, R S; Holmes, D M; Stanton, S L
Abstract : The mental state of 211 women attending a urodynamic clinic was assessed using questionnaires. Patients with genuine stress incontinence had scores comparable with other patients with longstanding physical complaints. Patients with sensory urgency were more anxious than those with genuine stress incontinence. Patients with detrusor instability were as anxious as patients with sensory urgency and in addition had higher scores on the hysteria scale. A subset of patients (roughly a quarter of the total) was identified, comprising members of all three diagnostic groups, for whom urinary symptoms rendered life intolerable. These patients were as anxious, depressed, and phobic as psychiatric inpatients, emphasising the serious psychological morbidity experienced by patients with urinary symptoms. Fifty patients with detrusor instability or sensory urgency entered a randomised trial comparing psychotherapy, bladder drill, and propantheline. The psychotherapy group significantly improved on measures of urgency, incontinence, and nocturia, though not on frequency. Bladder training was an effective treatment for frequency and patients became less anxious and depressed. There was a modest improvement in frequency of micturition in patients given propantheline. Frequency may be a learnt disorder which responds to the direct symptom oriented approach of bladder training. Patients with urgency and nocturia predominating might derive more benefit from psychotherapy.